Blasphemy, insult and hatred: finding answers in a democratic society (Science and technique of democracy no. 47, 2010)
Report by the Venice Commission -- Council of Europe texts on respect for others' culture and beliefs -- Exerpts from reports presented at the international round-table conference on Art and Sacred Beliefs : from Collision to Co-existence -- Art and sacred beliefs : from collision to co-existence Gianni Buquicchio -- Art and religious beliefs : the limits of liberalism Nicos C. Alivzatos -- Ethics of responsibility for artists Boualem Bessaih -- Art can legitimately offend Dimitris Christopoulos and Dimitri Dimoulis -- Whose responsibility? The case of Iran Karim Lahidji -- Intersection between freedom of expression and freedom of belief : the position of the United Nations Ariranga G. Pillay -- Blasphemy in the Greek Orthodox legal tradition Dimitris Sarafianos -- Blasphemy and justice in a Greek Orthodox context Michael Tsapogas -- Conflicts between fundamental rights : contrasting views on Articles 9 and 10 of the European Convention on Human Rights Françoise Tulkens -- Reshaping religion and religious criticism in ultramodernity Jean-Paul Willaime -- Conclusions Pieter van Dijk -- Appendices to the Report by the Venice Commission. I Collection of European national laws on blasphemy, religious insult and incitement to religious hatred II Analysis of domestic laws on blasphemy, religious insult and inciting religious hatred, on the basis of replies to a questionnaire